IR linewidth and intensity amplifications of nitrile vibrations report nuclear-electronic couplings and associated structural heterogeneity in radical anions. Issue 36 (17th August 2021) - Yan, Juchao; Wilson, Reid W.; Buck, Jason T.; Grills, David C.; Reinheimer, Eric W.; Mani, Tomoyasu
Abstract : Quantification of the intensity and linewidth of the ν (CN) IR band in a series of neutral and anionic nitrile-functionalized oligophenylenes reveals that the CN vibration is coupled to nuclear and electronic structural changes. Abstract : Conjugated molecular chains have the potential to act as "molecular wires" that can be employed in a variety of technologies, including catalysis, molecular electronics, and quantum information technologies. Their successful application relies on a detailed understanding of the factors governing the electronic energy landscape and the dynamics of electrons in such molecules. We can gain insights into the energetics and dynamics of charges in conjugated molecules using time-resolved infrared (TRIR) detection combined with pulse radiolysis. Nitrile ν (CN) bands can act as IR probes for charges, based on IR frequency shifts, because of their exquisite sensitivity to the degree of electron delocalization and induced electric field. Here, we show that the IR intensity and linewidth can also provide unique and complementary information on the nature of charges. Quantifications of IR intensity and linewidth in a series of nitrile-functionalized oligophenylenes reveal that the CN vibration is coupled to the nuclear and electronic structural changes, which become more prominent when an excess charge is present. We synthesized a new series of ladder-type oligophenylenes that possess planar aromatic structures, as revealed by X-ray crystallography. Using these, we demonstrate that CN vibrations can report charge fluctuations associated with nuclear movements, namely those driven by motions of flexible dihedral angles. This happens only when a charge has room to fluctuate in space.